(6^?)^-4 = 6^20

At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Get our expert's

answer on brainly

SEE EXPERT ANSWER

Get your free account and access expert answers to this and thousands of other questions.

A community for students.

(6^?)^-4 = 6^20

Mathematics
See more answers at brainly.com
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Get this expert

answer on brainly

SEE EXPERT ANSWER

Get your free account and access expert answers to this and thousands of other questions

@Lady.Liv1776 @Nnesha @pooja195 Pls help
\[\huge\rm (6^?)^{-4} = 6^{20}\] am ir right ?
Yes

Not the answer you are looking for?

Search for more explanations.

Ask your own question

Other answers:

exponent rule \[\huge\rm (x^m)^n=x^{m \times n}\]
m=20*(-4) ?
well m is missing exponent n =-4 so basically thats mean m times n = -20
okay i kinda get it
\[\huge\rm (6^\color{ReD}{?})^{\color{blue}{-4}} = 6^{\color{purple}{20}}\] \[\huge\rm (x^\color{Red}{m})^\color{blue}{n}=x^{\color{red}{m} \times\color{blue}{ n}} =x^{\color{purple}{mn}}\]
\(\color{blue}{\text{Originally Posted by}}\) @pielover123 m=20*(-4) ? \(\color{blue}{\text{End of Quote}}\) this should be -4 * m = 20
Okay so -4*m which is -4m then times it by 20? which would be -80m?
why did you mutliply -4m by 20 ?
-4m =20 how would you solve for m ?
in other words m times n = 20 -4 times what = 20 ?
-4*5 right?
-4 times 5 = ??
is -20
now look at the original question is it 6^{-20} ?
Im confused now sorry
let samy missing exponent is m \[\huge\rm (6^m)^{-4}=6^{m \times -4}=6^{20}\] m would be what ?
-4 times 5 = -20 but there is positive 20
so make them all a negative?
what do you mean by `all` 20 as well ?
yes
or you can set it like this -4m =20 solve for m
we have to prove it that left side is equal to right side we can't change the right hand side
\[\rm -4m=20\] solve for m plz
5 right?
20/-4= ?
remember `negative ` times ` negative` = positive `negative ` divide by `negative` = positive
negative times positive = negative negative divide by positive number = negative
so it s -5 then
yes right!
-4 times -5 = 20
6^-5 is right then
yep right
thanks :D
np D:

Not the answer you are looking for?

Search for more explanations.

Ask your own question